Cultures of alveolocytes I and II type for medical and ecological research - Yurkevich, Mariya Yu.; Alchovik, Pavel V.; Tsarik, Anastasia A.; Kokhniuk, Marina A. (Journal of the Belarusian State University. Ecology, 2021)
The alveolar epithelium is a dynamic tissue, consisting of cells of types I and II, covering more than 99 % of the lung inner surface and actively responding to various endogenous and exogenous stimuli. The technology of alveolocyte isolation is presented, which consists in mechanical disaggregation of tissue with subsequent processing of the resulting explants with 0.25 % trypsin solution in combination with filtration of the cell suspension through pores with a diameter of 100 μm and 50 μm. In two-dimensional static culture viable actively dividing rounded cells and large alveolar epithelial cells with cuboid or polygonal morphology, producing surfactant proteins, were visualized.